Evaluation of the operation results of the ultra-fast earthquake reporting system of the Zigong Station Network - Jun Du (地震科学进展, 2022)
The ultra-fast earthquake reporting system can automatically determine the three elements of an earthquake within a few seconds to tens of seconds after the earthquake. The system has been deployed in Zigong Digital Telemetry Seismic Network Center for trial operation since December 2018. After analyzing the automatic positioning results from the trial operation of the system from January 2019 to January 2020, it is found that the ultra-fast reporting system improves the time of automatic quick reporting of Zigong earthquake from minute level to second level. The positioning accuracy meets the requirements of earthquake quick reporting, which can meet the needs of Zigong earthquake emergency work. The causes of errors are also analyzed.